2009
DOI: 10.1038/clpt.2009.244
|View full text |Cite
|
Sign up to set email alerts
|

CD11c as a Transcriptional Biomarker to Predict Response to Anti-TNF Monotherapy With Adalimumab in Patients With Rheumatoid Arthritis

Abstract: We performed transcription profiling using monocytes to identify predictive markers of response to anti-tumor necrosis factor (anti-TNF) therapy in patients with rheumatoid arthritis (RA). Several potential predictors of response were identified, including CD11c. Validation in samples from independent cohorts (total of n = 27 patients) using reverse transcription-PCR confirmed increased expression of CD11c in responders to adalimumab (100% sensitivity; 91.7% specificity, power 99.6%; alpha = 0.01). Pretherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 50 publications
0
54
1
4
Order By: Relevance
“…Why some patients never respond is intriguing, and efforts have been made using biomarker studies to identify response to therapy, but none have been validated. A study based on a genome-wide association scan suggests a complex multigenetic basis for response or resistance to therapy (34)(35)(36). Secondary nonresponsiveness after a successful initial response does appear, in part, to be related to the immunogenicity of the therapeutic Ab (37).…”
mentioning
confidence: 99%
“…Why some patients never respond is intriguing, and efforts have been made using biomarker studies to identify response to therapy, but none have been validated. A study based on a genome-wide association scan suggests a complex multigenetic basis for response or resistance to therapy (34)(35)(36). Secondary nonresponsiveness after a successful initial response does appear, in part, to be related to the immunogenicity of the therapeutic Ab (37).…”
mentioning
confidence: 99%
“…A strength of this study was the large sample size tested relative to previous treatment response gene expression profiling studies and the use of samples from extreme ends of the response spectrum, which resulted in greater power to detect the same effect size as previously reported in the study of adalimumab-treated patients [12]. For example, in the original study, after initial identification of CD11c expression associating with treatment response in 7 patients by microarray analysis, validation was conducted in 27 patients from an independent cohort by RT-PCR [12].…”
Section: Discussionmentioning
confidence: 96%
“…For example, in the original study, after initial identification of CD11c expression associating with treatment response in 7 patients by microarray analysis, validation was conducted in 27 patients from an independent cohort by RT-PCR [12]. By contrast, the current study of 75 RA samples is, to the best of our knowledge, one of the largest and most well-powered treatment response studies of gene expression conducted to date in RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since biomarkers to predict response are available not only from the autoantibody profile (as part of the immunome), but may also be encoded in the genes (the genome) or provided by the composition of mRNA expression (the transcriptome), proteins, and metabolites (proteome and metabolome), the field for future research is wide open. For example, transcription profiling on monocytes revealed that increased expression of CD11c at baseline is associated with response to adalimumab monotherapy in patients with RA 5 . In this issue of The Journal Tsuzaka, et al identify mRNA expression levels of ADAMTS-5 as a novel predictive marker for response to a TNF-blocking agent 6 .…”
mentioning
confidence: 99%